Comparison of Shear Bond Strength of Orthodontic Brackets with Fifth and Eighth Generation Adhesive Systems - Qasim Khalid, Muhammad Imran Rahbar, Naseer Ahmad Chaudhry, Asim Riaz, Anum Aziz, Saadia Ata, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Self-etching primers (SEPs) has streamlined orthodontic braces placementprocess by minimizingclinical process, chairside time and has enhanced patient comfort. Materials & Methods: 60 untreated extracted premolars from all quadrants of jaws of males and females, aged between 12-35 years, were included. Defective, restorative and anomalous premolars were excluded. Attachment of brackets on the facial surface, with composite (Transbond XT 3M UNITEK) which then was cured for 20 seconds by a light source, using Transbond XT (fifth generation) and Futurabond DC (eighth generation) as bonding agents was done. Universal testing machine was used to test Shear bond strength (SBS), in COMSATS. Results: Group 1 had 22.87 ± 6.08 years as average age,whilegroup 2 had 20.67 ± 5.20years.34 patients (56.67%) were males and 26 (43.33%) were females. Group 1 (fifth generation) had an average SBS of 16.40 ± 3.47 MPa, and in Group 2 (eight generation), it was 34.9 ± 4.02 MPa. Conclusion: The research concluded, that in brackets average SBSwith generation eight wass superiorto the onesattached with fifth generation adhesive. Keywords: SBS, Self-etching primer, Orthodontic adhesive